Palladium-Prussian blue nanoparticles; as homogeneous and heterogeneous electrocatalysts - Pandey P.C.; Singh S.; Walcarius A. (My University, 2025)
We report herein a synthetic strategy based on the use of tetrahydrofuran hydroperoxide (THF-HPO) that allows controlled conversion of palladium ion and potassium ferricyanide into palladium nanoparticles (PdNP) and water soluble Prussian blue nanoparticles (PBNP) respectively. The results revealed that THF-HPO provide a medium to enable the transformation of 3-aminopropyltrimethoxysilane (3-APTMS) capped palladium ions into PdNP of desired nanogeometry viz. PdNP1 and PdNP2. The processability of these two types of nanomaterials enabled the formation of PB-PdNP1 and PB-PdNP2 having potentiality for use either as homogeneous suspension or in heterogeneous matrix. The results based on peroxidase mimetic activity, cyclic voltammetry and amperometry revealed the gradual improvement in analytical performances of as synthesized nanomaterials as a function of palladium size and has been characterized by TEM, HRSEM and EDX analysis. © 2018 Elsevier B.V.